Neutrophil activation and nucleosomes as markers of systemic inflammation in paroxysmal nocturnal hemoglobinuria: effects of eculizumab. (19th October 2015) - van Bijnen, S. T. A.; Wouters, D.; van Mierlo, G. J.; Muus, P.; Zeerleder, S.
Summary: Background: Paroxysmal nocturnal hemoglobinuria (PNH) is characterized by complement‐mediated hemolysis and a high risk of life‐threatening venous and arterial thrombosis. Uncontrolled complement activation and the release of cell‐free heme may result in systemic inflammation, neutrophil activation, and the release of procoagulant neutrophilic proteases. Eculizumab, an antibody to complement factor C5, inhibits hemolysis and reduces thrombotic risk. Objectives: To study neutrophil activation and nucleosome levels in relation to thrombosis in PNH patients before and during treatment with eculizumab. Patients/methods: In 51 untreated PNH patients, including 20 patients before and after commencing eculizumab treatment, we have assessed neutrophil activation by measuring elastase‐α1 ‐antitrypsin (EA) complexes and circulating nucleosomes, as established markers for systemic inflammation and cell death. Results: Nucleosomes (median; range; 95% confidence interval [CI]), but not EA complexes, were higher in PNH patients with a history of thrombosis (16; 7–264; 0.3–94 U mL −1, n = 12) than in those without (6; 6–35; 7–11 U mL −1, n = 39) or controls (8; 6–23; 7–12 U mL −1, n = 17). EA complexes, but not nucleosomes, decreased promptly and markedly upon eculizumab treatment. EA complexes (estimated marginal means; 95% CI) remained low at ≥ 12 weeks (50; 34–67) compared with baseline (12; −6 to 29). Conclusions: The increased nucleosome levels in PNH patients with a history of thrombosis suggest systemic inflammation and/or cell death. Neutrophil activation markers did not differ between patients with and without a history of thrombosis and healthy controls. Interestingly, basal neutrophil activation in PNH patients significantly decreases on treatment with eculizumab, indicating that neutrophil activation is C5a driven.